Are 2 cords better than 1? - Shpall, Elizabeth (American Society of Hematology, 2007)
In this issue of Blood, Brunstein and colleagues describe the use of nonmyeloablative conditioning and double umbilical cord blood transplantation (UCBT) for treatment of adult patients.